Editor's Highlight: Glutathione S-Transferase Activity Moderates Methylmercury Toxicity During Development in Drosophila - Vorojeikina, Daria (Toxicol Sci, 2017)
Glutathione (GSH) pathways play a central role in methylmercury (MeHg) metabolism and elimination, largely due to formation of a more readily transported MeHg-GSH conjugate. Glutathione S-transferases (GSTs) have therefore been proposed to facilitate MeHg elimination by catalyzing MeHg-GSH conjugation. A role for human GSTP1 in MeHg disposition is suggested by the association of two common polymorphisms in the coding region (Ile105Val and Ala114Val) with Hg levels in either blood or hair. In this study, we investigated a functional role for GSTs in modulating MeHg toxicity during development. Using the Drosophila model to execute targeted manipulations of both endogenous GSTs and introduced human GSTP1 variants we correlate gene and protein expression levels with GST activity and also with MeHg body burden and developmental outcomes. RNAi knockdown of endogenous GSTD1, GSTE1, or GSTS1, individually, increased susceptibility to MeHg during pupal development resulting in a reduced rate of adult eclosion. Exogenous expression of human GSTP1 in developing flies resulted in increased MeHg tolerance relative to control flies as seen with elevated eclosion rates when reared on MeHg containing food. Furthermore, the GSTP1(105) and GSTP1(114) variants showed a reduced enzyme activity relative to wild-type GSTP1 (GSTP1(wt)). Finally, we observed a trend whereby Hg body burden was inversely related to the levels of GST activity. However, in some instances GSTP1 expression resulted in increased eclosion rates without reducing Hg body burden suggesting that GSTs interact with MeHg via both toxicokinetic and toxicodynamic mechanisms. These findings indicate that GSTs moderate MeHg toxicity during development in our experimental model.